Forearm bone mineral density as a predictor of reduction loss in distal radius fractures treated with cast immobilization - Cho, Sung Tan; Kim, Jin Hwan; Lee, Sung San; Lee, Yong Jae; Lee, Hyun Il (Frontiers in Surgery, 2022)
Objective: Many potential predictors have been identified and proposed for predicting late reduction loss in distal radius fractures. However, no report exists on whether the bone mineral density (BMD) of the forearm correlates with the loss of reduction in distal radius fractures. This study aimed to investigate whether forearm BMD can be used as a predictor of reduction loss in distal radius fractures treated with cast immobilization Methods: Ninety patients with distal radius fractures were divided into two groups according to the maintenance or loss of reduction evaluated from radiographs taken at least 6 weeks after their injury. Lumbar and forearm BMD (total and metaphysis) T-scores were measured and compared between the maintenance of reduction (MOR) group and the loss of reduction (LOR) group. Additionally, serologic markers (C-terminal telopeptide, osteocalcin, vitamin D) and radiologic risk factors (intra-articular fracture, ulnar fracture, dorsal comminuted fracture, volar hook) were evaluated and a logistic multiple regression analysis was performed to know the main risk factors of reduction loss. Results: Reduction loss was observed in 38 patients (42.2%). The total and metaphyseal BMD of the forearm was less in the LOR group than in the MOR group. However, the difference was not statistically significant [-2.9 vs. -2.5 for total (p=0.18), -2.3 vs. -2.0 for metaphysis (p=0.17)]. Multiple logistic regression analysis showed initial dorsal comminution (p=0.008) and ulnar variance (p=0.01) were the main risk factors for reduction loss. Conclusions: Forearm BMD was not a valuable prognostic factor for reduction loss in distal radius fractures. Initial dorsal comminution and ulnar variance rather than forearm BMD should be considered preferentially when predicting which patients are at high risk of reduction loss in distal radius fractures.